Análisis del crédito de desarrollo humano otorgado al sector Sergio Toral I, parroquia Tarqui, provincia del Guayas - Quinde Cevallos, Jimmy Andrés (2021)
This research aims to analyze the granting of the Human Development Credit to families in Sergio Toral I, sector in the northwest of the city of Guayaquil. Having as review theories that allow to contribute to this research topic both in the social and economic context, emphasizing the importance of promoting solid economies that allow to generate the human development of a country and achieve the objective set out in the National Plan of the Good Live to meet its needs and dignified life. The focus of this research is to know the process of those who access this benefit as they give the use to monetary transfer, measuring through the research instrument applied to the sample of the beneficiaries to carry out the respective analysis, developing a FODA analysis of the most relevant results of the research and providing with an action plan that allows the competent entity to achieve the objectives established in public policy with the beneficiaries of the Human Development Credit and thus use the respective discussion of the results obtained and the preparation of the final report with their respective conclusions and recommendations that will serve as evidence for future research.......